Teachers’ conceptual understanding of inquiry-based approach (IBA) at secondary schools in Tanzania - Mushi Saumu Athumani; Ismail Sheikh Ahmad; Nik Suryani Nik Abdul Rahman (Association for Scientific Computing Electrical and Engineering(ASCEE), 2021)
The purpose of this qualitative study was to explore conceptual understanding of geography teachers of Inquiry-Based Approach (IBA) for teaching Geography subject. The researcher adopted the case study research design, and the study was conducted on eleven geography teachers from four Secondary schools at Morogoro Municipality, Tanzania. The findings indicate a mixed conceptual understanding of the interviewed geography teachers on the meaning of IBA although some of them seems to experience the use IBA features in their teaching. A lesson can be drawn from this study to inform the area of teaching and teachers development in Tanzania. The study recommended that to make the most use of inquiry-based approach of teaching and learning especially in geography subject, teachers have to be updated now and then on how to effectively use it in the classroom.